A Comparative Study to Evaluate Health Outcomes Regarding The Effect of Rosacea on Eye Health in Iraqi Patients - Mahmood, Dr. Omar Salim (Central Asian Journal of Medical and Natural Science, 2025)
Rosacea is a chronic inflammatory skin condition that frequently presents with ocular symptoms, yet its impact on eye health remains underrecognized in clinical settings. The link between dermatological and ocular manifestations is often overlooked, leading to delayed diagnosis and suboptimal management. This study addresses this gap by conducting a cross-sectional observational comparison of ocular health outcomes in 160 Iraqi adults—120 with rosacea and 40 healthy controls. Standardized questionnaires (DLQI and OSDI), clinical ophthalmologic assessments, and oxidative stress biomarker analyses were employed. The findings reveal significantly higher rates of ocular comorbidities, including blepharitis (55% vs 25%, aOR = 6.50, p<0.001), dry eye syndrome, and conjunctivitis in rosacea patients. Schirmer’s test and tear break-up time results were markedly lower among rosacea patients, indicating impaired tear film. Quality of life scores were significantly worse in the rosacea group. Additionally, oxidative stress markers (TOS, OSI) were elevated, while antioxidant levels (TAS, ARE) were reduced, suggesting a possible pathophysiological mechanism. The study concludes that ocular involvement in rosacea is clinically significant, requiring interdisciplinary awareness and management. Early screening for ocular symptoms and integration of dermatological and ophthalmological care can improve patient outcomes and prevent vision-threatening complications.